Perlakuan Lokasi Penanaman dan Pemberian Pupuk KCl terhadap Serangan Cendawan Patogen pada Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) di Main –Nursery - Nurul Hidayati; Pienyani Rosawanti; Sayuti Sayuti (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Pathogen attacks often occur on oil palm plants, particularly on the central nursery. Factors that affect the attack are plant and environmental factors. This study aims to determine the location of planting (temperature and humidity) and the administration of KCL fertilizer on the invasion of fungal pathogens on oil palm plants (Elaeis guineensis Jacq.) In nurseries (Main - nursery). This research was carried out on Jalan Jendral Sudirman Km. 9, Pasir Putih Village, Baamang District, East Kotawaringin Regency, Sampit. The testing of palm oil seedling samples was carried out at the Plant Quarantine Laboratory, Palangka Raya Class II Agricultural Quarantine Center. The design of this study was Split Plots Design. The planting location factors were considered to be more influential, so they are placed as main plots with three levels, namely the location of the greenhouse, open space and using 80% paranet and KCL fertilizer as a subplot with two levels. Each plot was compiled with RAL with four replications. The results of the study obtained both planting systems, environmental factors in the form of temperature and humidity, as well as giving KCl fertilizer as a whole have a significant effect on the growth of fungal pathogens on oil palm plants. In cultivating oil palm plants, it is recommended to use the planting system in open land by providing KCl fertilizer.